Beyond the law: trafficking, slavery, servitude, forced labour and abandonment - Segrave, Marie Therese (The borders of violence, 2024)
Our focus in this chapter is on the intersection of DFV, human trafficking and slavery. We argue that the demarcation of forms of violence in law and policy has significant implications, including how we understand women's experiences of victimisation, how the state responds to DFV and, critically, what violence is seen and not seen. We examine how experiences of DFV align with the criminal offences of trafficking and slavery-like practices in Australia. We engage with critical accounts of the ways in which the state positions itself as the benevolent actor, responding to forms of violence defined in law and policy in very narrow ways, with no attention to the consequences for victim-survivors. We consider the challenges arising from the lack of recognition of women's labour in the private familial space, which tends to fall both outside of employment protections and outside of the focus of much of the work of DFV supports. We raise concerns about the move in Australia and elsewhere to articulate that modern slavery and DFV intersect, with little to no engagement with the impacts of the migration system and border systems in terms of sustaining violence, abuse and exploitation against temporary migrant women.